The Impact of ICT on Working from Home: Evidence from EU Countries - Vahagn Jerbashian; Montserrat Vilalta-Bufi (Global Labor Organization (GLO), 2020)
We use data from 14 European countries and provide evidence that the fall in prices of information and communication technologies (ICT) is associated with a significant increase in the share of employees who work from home. Similar results hold within age, gender, and occupation groups. There are notable differences across age groups, however. The effect of the fall in ICT prices on working from home increases with age. A rationale for such a result is that the preference for working from home increases with age.
Keywords: J23; J24; O33; 330; Working from Home; ICT; Age; Gender; Occupations